Diagnosis of Langerhans cell histiocytosis on cytological examination of cerebrospinal fluid: Report of the first case. Issue 12 (11th August 2022) - Tommasino, Francesco; Cardamone, Chiara; Tortora, Vincenzo; Sabbatino, Francesco; Di Sarno, Chiara; Caputo, Alessandro
Abstract: Langerhans cell histiocytosis (LCH) is a disease of unknown etiology characterized by a proliferation of histiocytic cells resembling dendritic Langerhans cells. LCH can be unifocal or multifocal, with one‐ or many‐organ involvement. The serous fluids are rarely involved. Cytological diagnosis of LCH is possible and relies on recognition of the typical cytomorphological features and subsequent immunocytochemical confirmation. Given the possibility of multisystem involvement, after diagnosing LCH it is necessary to carry out staging exams such as a bone survey, abdominal ultrasound, complete blood count, screening for diabetes insipidus and pulmonary function tests. We present the first case of LCH where the diagnosis was reached on cytological material from the cerebrospinal fluid. To the best of our knowledge, this is the first such case reported in the international literature to date. The morphological and immunocytochemical characteristics of our case are described, and the relevant literature is reviewed